Effects of Grammatical Structure of Compound Words on Word Recognition in Chinese - Cui, Lei; Cong, Fengjiao; Wang, Jue; Zhang, Wenxin; Zheng, Yuwei; Hyönä, Jukka (Frontiers in Psychology, 2018)
Two lexical priming experiments were conducted to examine effects of grammatical structure of Chinese two-constituent compounds on their recognition. The target compound words conformed to two types of grammatical structure: subordinate and coordinative compounds. Subordinate compounds follow a structure where the first constituent modifies the second constituent (e.g., ,meaning snowball); here the meaning of the second constituent (head) is modified by the first constituent (modifier). On the other hand, in coordinative compounds both constituents contribute equally to the word meaning (e.g., , wind and rain, meaning storm where the two constituent equally contribute to the word meaning). In Experiment 1 that was a replication attempt of Liu and McBride-Chang (2010), possible priming effects of word structure and semantic relatedness were examined. In lexical decision latencies only a semantic priming effect was observed. In Experiment 2, compound word structure and individual constituents were primed by the prime and target sharing either the first or second constituent. A structure priming effect was obtained in lexical decision times for subordinate compounds when the prime and target compound shared the same constituent. This suggests that a compound word constituent (either the modifier or the head) has to be simultaneously active with the structure information in order for the structure information to exert an effect on compound word recognition in Chinese. For the coordinative compounds the structure priming effect was non-significant. When the meaning of the whole word was primed (Experiment 1), no structure effect was observable. The pattern of results suggests that effects of structure priming are constituent-specific and no general structure priming was observable.